2011
DOI: 10.1016/j.jphotobiol.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Basal and squamous cell carcinoma risks for golfers: An assessment of the influence of tee time for latitudes in the Northern and Southern hemispheres

Abstract: This study investigates the influence of tee time to determine the relative basal cell carcinoma (BCC) exposure calculations was used to determine BCC and SCC risk factors for golfers using a regular weekly tee time. Relative risk was found to be proportional to golf tee time with mid morning tee times generally presenting the greatest risk in each latitude range. The greatest contribution toward the risk of developing basal and squamous cell carcinoma was found to occur for golfers beginning weekly rounds m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
1
22
1
Order By: Relevance
“…Our study showed that the most affected people were farmers and herders who were repeatedly exposed to sunlight for long periods of time. Previous studies also highlight the role of long-term exposure to sunlight on people who work outdoors or perform physical exercises in open environments, which predispose these individuals to NMSC (5,7,8). Radespiel et al in a report from Germany in 2009 described that outdoor jobs and contact with sunlight are mostly accompanied by BCC, a finding in harmony with the results of the present study (6).…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that the most affected people were farmers and herders who were repeatedly exposed to sunlight for long periods of time. Previous studies also highlight the role of long-term exposure to sunlight on people who work outdoors or perform physical exercises in open environments, which predispose these individuals to NMSC (5,7,8). Radespiel et al in a report from Germany in 2009 described that outdoor jobs and contact with sunlight are mostly accompanied by BCC, a finding in harmony with the results of the present study (6).…”
Section: Discussionsupporting
confidence: 91%
“…The practice of sport is highly recommended by health organizations due to its beneficial effects on the cardiovascular system, but it must be borne in mind that sportsmen/women are potentially exposed to excessive doses of solar UVR, especially during training sessions on hot days. Several studies indicating the occurrence of skin melanomas in marathon runners, 20,21 cyclists, 22 mountain guides 23 and golfers 24 support the idea that participating in outdoor sports can increase the risk of skin cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Some recent studies show that the incidence of melanoma is related to both altitude and latitude (Aceituno et al 2011;Boniol et al 2005;Chang et al, 2009;de Vries et al, 2004;Downs et al, 2011;Micu et al, 2011;Moehrle and Garbe, 1999;Pfeifer et al, 2006). Due to its geographical situation, for most of the year the Valencia Region (Spain) receives large doses of UVR.…”
Section: Introductionmentioning
confidence: 99%